The Relationship between High Altitude Work Environments and Anxiety among Employees - Djula, Sapti Heru Widiyarti; Tambunan, Evelyn Hemme (Universitas Padjadjaran, 2025)
The present study examines the relationship between high altitude and anxiety levels among employees at one of Indonesia’s leading petrochemical company. Using a quantitative research design, the investigation focused on 42 employees working in distinct altitude zones within the facility. Data were collected over a six month period during normal operational hours, employing the Hamilton Anxiety Rating Scale (HARS) as the standardized psychological assessment tool. Altitude measurements for work zones were recorded precisely, with categorized levels defines as low, moderate, high and very high altitude zone. Descriptive statistics, including means, standard deviations, and range values, were computed and correlation tests conducted R programming to determine the strength and direction of the relationship between altitude and anxiety. Results revealed the mean HARS scores among 42 participants was 21.4 (SD = 5.7), with a range of 11 to 33 whilst a statistically significant positive correlation between increased altitude exposure and elevated anxiety scores (r = 0.68, p < 0.001), suggesting that higher work zone are associated with greater anxiety levels among employees. This study also discusses occupational health and safety concerns, ethical considerations, and the limitations intrinsic to a cross-sectional quantitative design. Implications for workplace design and employee well-being interventions are explored, with recommendations for future research addressing broader environmental and psychosocial variables.